Financing Moroccan SMES: Analysis of the influencing factors and the crucial role of the government guarantee scheme - Oussouadi Kamal; Cherkaoui Kenza (Investment Management & Financial Innovations)
This study uses a quantitative approach to examine the determinants of SME financing in Morocco. The sample consists of 500 Moroccan SMEs that have submitted applications for bank finance, with their applications being assessed for a possible government credit guarantee. The sample includes companies that obtained state-guaranteed bank financing, those whose applications were rejected but that obtained other financing, and those that did not obtain financing, all evaluated in the year following the application. The analysis is based on nominal logistic regression to examine the interactions between different variables, including the amount of credit requested, profitability, debt level, repayment capacity, size, managerial shareholding, decision-making maturity, and the presence of a government credit guarantee. Following careful collection and analysis of the data, a number of results were drawn. In particular, it emerged that high profitability, solid repayment capacity, a minimum size requirement, an appropriate level of debt, high decision-making maturity and the presence of a government credit guarantee are significant factors that increase the likelihood of obtaining financing. On the other hand, the amount of credit requested and the manager’s shareholding did not show any significant impact on the probability of obtaining financing.